Second law analysis of viscous flow through rough tubes subjected to constant heat flux. (11th May 2006) - Abdel-Moneim, S.A.; Ali, R.K.
Entropy generation for a viscous, forced convection through enhanced rough tubes subjected to constant heat flux was numerically investigated. The entropy generation and exergy destruction due to the flow friction and heat transfer was proposed to evaluate the benefits of the utilisation of different enhanced tubes. The model was based on either measurements or empirical correlations for both the flow and heat transfer characteristics in plain and enhanced tubes. Flow of different fluids in rough tubes with three-dimensional internal extended surfaces (3-DIES) were studied. Enhanced rough tubes, either with continued or regularly spaced tape inserts were investigated. Based on exergy performance, it was found that the use of hollow 3-DIES tubes in water turbulent flow regime is preferable while segmented twisted-tape inserts is attractive in laminar flow. Also, inline 3-DIES rough tubes indicate a lower exergy destruction rate when compared with that of staggered alignments. The correlation for both optimum Reynolds number (Re*) and minimum percentage exergy destruction (ψmin%) were obtained for oil and Ethylene Glycol flows in inline 3-DIES rough tubes as a function of the exposed heat flux, Prandtl number and the tube ratio (L/D).